The Reliability of Remembered Pretreatment Visual Analog Scale Scores among Hand-Surgery Patients - Finsen, Vilhjalmur; Hillesund, Sigrun; Fromreide, Ida (Journal of Hand and Microsurgery, 2019)
Background In clinical audits in which preoperative visual analog scale (VAS) scores were not recorded, it would be useful if such scores could be re-created at the time of review.Patients and Methods We recorded VAS score for pain during the past week before surgery for 245 consecutive hand-surgery patients scheduled for planned surgery during a 6-month period. A total of 30 patients who refused to participate or were unable to respond were excluded. The remaining 215 patients were contacted after 21 months and asked to furnish a new VAS score of the pain they remembered to have had during the last week before surgery. Responses were analyzed with a Bland-Altman plot.Results One hundred and thirty-one (61%) of the patients responded. The mean remembered preoperative score was higher than the mean real preoperative score in all diagnosis groups. The mean difference was 10 mm (standard deviation: 22 mm; standard error of the mean: 2 mm). The lower and upper limits of 95% agreement for individual scores were -33 and 53 mm, whereas the lower and upper limits of the 95% confidence interval of the mean were 6 and 14 mm.Conclusion It may be possible to predict the mean real preoperative VAS score in groups of patients with accuracy using the remembered preoperative score. In individual patients, remembered preoperative VAS scores are far too inaccurate to be of value. However, real preoperative scores should be used whenever possible.
Keywords: visual analog score; remembered; recall; accuracy; pain